Simple Assessment of Spatio-Temporal Evolution of Salt Marshes Ecological Services - Carrasco, A. Rita (Frontiers in Ecology and Evolution, 2019)
A number of previous research studies have addressed the enormous role played by biodiversity and ecosystems in human well-being and have placed particular emphasis on the consequences resulting from the reduction or loss of these services. A handful of studies have implemented practical methodologies to quantify the variability of limiting factors leading to reductions in these services. The aim of this article is to document the limited number of studies that have analyzed coastal ecosystem services and acknowledge the impacts of physical changes in habitat provision. In one example, it is clear that the maintenance of salt marshes depends on sedimentary supply and consequent morphological variability in spite of the fact that there is usually no recurrent integration of habitat time-space dynamics (sediment availability) during the quantification and monetization of marsh services (i.e. monetary valuation of salt marsh services). This means that one key challenge facing the analysis of salt marsh (or other ecosystem) services in a global climate context is to predict future value, based on past trends, while at the same time guaranteeing conservation. Research in this field has been very broad and so the use of long-term evolutionary datasets is proposed here to explain future habitat provision. An empirical approximation is also presented here that accounts for service provision and enables time-space analysis. Although improvements will be required, the equation presented here represents a key first step to enable managers to cope with the constraints of resource limitations and is also applicable to other habitats.